2003
DOI: 10.1002/ajpa.10163
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic plantar pressure distribution during terrestrial locomotion of bonobos (Pan paniscus)

Abstract: We collected high-resolution plantar pressure distributions of seven bonobos during terrestrial bipedal and quadrupedal locomotion (N = 146). Functional foot length, degree of hallux abduction, and total contact time were determined, and plots, showing pressure as a function of time for six different foot regions, were generated. We also studied five adult humans for comparison (N = 13). Both locomotion types of the bonobo show a large variation in plantar pressure distributions, which could be due to the inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
170
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 129 publications
(179 citation statements)
references
References 37 publications
8
170
0
1
Order By: Relevance
“…Compared with the consistent use of an HS gait in humans, many of the foot postures used by nonhuman apes lead to reduced total translation of the COP (Vereecke et al, 2003). For example, when bonobos land on both the heel and midfoot simultaneously (Elftman and Manter, 1935;Vereecke et al, 2003Vereecke et al, , 2005, the COP originates between the heel and forefoot, rather than directly under the heel. Therefore, a consistent HS landing posture that maximizes COP translation may be a novel evolutionary solution to lengthening inverted pendulum struts from an ape-like ancestral condition.…”
Section: Plantigrade Walking and Effective Limb Lengthmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with the consistent use of an HS gait in humans, many of the foot postures used by nonhuman apes lead to reduced total translation of the COP (Vereecke et al, 2003). For example, when bonobos land on both the heel and midfoot simultaneously (Elftman and Manter, 1935;Vereecke et al, 2003Vereecke et al, , 2005, the COP originates between the heel and forefoot, rather than directly under the heel. Therefore, a consistent HS landing posture that maximizes COP translation may be a novel evolutionary solution to lengthening inverted pendulum struts from an ape-like ancestral condition.…”
Section: Plantigrade Walking and Effective Limb Lengthmentioning
confidence: 99%
“…For example, researchers have shown that our closest living relatives, bonobos (Pan paniscus) and common chimpanzees (Pan troglodytes), use a wide range of landing postures, from a traditional human-like heel strike, to landings where the heel does not touch down until the second half of stance phase (see Elftman and Manter, 1935;Vereecke et al, 2003). Most often, these apes use gaits where the heel and mid-foot contact the ground simultaneously, which also differ from human HS walking where initial ground contact is made by the heel alone (Elftman and Manter, 1935;Vereecke et al, 2003). Thus, the key human evolutionary shift from the non-hominin ape foot landings appears to be the consistent use of heel-only landing postures.…”
Section: Introductionmentioning
confidence: 99%
“…The average force profile during swimming was obtained by first subdividing the total extension time into 21 equal steps by weighted interpolation, and then taking the average and standard deviation for each step from the eight sequences (Vereecke et al, 2003) from two animals.…”
Section: Force Calculations During Swimming Based On Dpiv Datamentioning
confidence: 99%
“…Recently, efforts have been made to compile a sound quantitative data set of gait variables for great apes (Aerts et al, 2000;D'Août et al, 2002;Isler and Thorpe, 2003;Isler, 2005;Vereecke et al, 2003Vereecke et al, , 2004. The lack of information for gibbon locomotion is unfortunate because insights into their locomotor capacities could add to our understanding of hominoid locomotion and perhaps the evolution of habitual terrestrial bipedalism in humans.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, bipedal gait characteristics of gibbons were compared to those of bonobos (Pan paniscus) and humans (Homo sapiens). These species are interesting for comparison, in view of their different morphology, their ability to walk bipedally, and their close phylogenetic relationship with gibbons (McHenry and Corruccini, 1981;Goodman, 1999;Aerts et al, 2000;Vereecke et al, 2003;D'Août et al, 2004;Goodman et al, 2005).…”
Section: Introductionmentioning
confidence: 99%